Penerapan Metode Technology Acceptance Model (TAM) Dalam Penggunaan Aplikasi Linkaja - Hasada Satria Putra Pratama; Diovianto Putra Rakhmadani (JURIKOM (Jurnal Riset Komputer), 2022)
Financial technology is a financial service where the government and the public really expect its usefulness to increase users of the financial service system, for example the LinkAja application. LinkAja is an e-wallet or digital wallet application that allows users to make non-cash transactions, such as offline shopping or other offline transactions. Based on feedback data in several digital service stalls, the LinkAja application is known to have a lot of negative perceptions about its usefulness and there are also many who have difficulty operating the application, including the Telkom Institute of Technology Purwokerto (ITTP). The purpose of this study is to see the acceptance of the LinkAja application at the Telkom Institute of Technology Purwokerto with the Technology Acceptance Model (TAM) method from indicators of perceived usefulness, ease of use, behavioral interest in using, and actual system use. To obtain data when compiling this final project, the data collection instruments used were observation and distributing questionnaires using statistical data processing software (SPSS). In this study, it was found that the direct influence with the highest level of significance value was perceived usefulness on actual system use of 0.582 > 0.05 and the most dominant indirect effect or with the highest total value, namely perceived ease of use on Actual System Use. through behavioral intention to use with a total of 0.39